Taxonomic revision of the African assassin bug genus Fusius (Heteroptera: Reduviidae: Peiratinae) - Liu, Yingqi; Li, Hu; Cai, Wanzhi (European Journal of Taxonomy, 2023)
The African assassin bug genus Fusius Stål, 1862 is revised after the examination of type specimens with redescriptions of four species. Lectotypes of Pirates (Fusius) H-flavum Reuter, 1881 and Pirates rubricosus Stål, 1855 are designated. The status of P. (Fusius) H-flavum Reuter, 1881 is revalidated with its current name as F. hflavus (Reuter, 1881) stat. rev. et comb. nov. Seven new synonyms are proposed: F. dilutus Miller, 1957 = F. gowdeyi Miller, 1957 syn. nov. = F. liberiensis Miller, 1957 syn. nov. = F. dilutus anonymus Dispons, 1969 syn. nov. = F. dilutus vicinus Dispons, 1969 syn. nov.; F. distinctus Miller, 1957 = F. sylvestris Miller, 1957 syn. nov.; F. hflavus (Reuter, 1881) = F. hargreavesi Miller, 1957 syn. nov.; F. rubricosus (Stål, 1855) = F. ugandensis Miller, 1957 syn. nov. A key is provided to separate the four species of this genus. Diagnosis and distribution of Fusius are briefly discussed.